PENGARUH JIGSAW PUZZLE TERHADAP PENINGKATAN KEKUATAN OTOT EKSTREMITAS ATAS PADA PASIEN STROKE - Nisfil Mufidah; Dwi Nurus Samsiyah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2020)
Stroke is a cerebrovascular disease that can cause a decrease in muscle strength in the extremities. Based on a preliminary study at Anna Medika Madura General Hospital, it was obtained from 10 respondents of stroke patients who had normal muscle strength of 2 people, scale 1 (1 person), scale 2 (2 people), scale 3 (2 people), and scale 4 (4 people) ). These data indicated low limb muscle strength in stroke patients. The purpose of this study is to analyze the effect of jigsaw puzzles on increasing the strength of upper limb muscles in stroke patients at Anna Medika Madura General Hospital. The research design used Quasy-Experiments. The independent variable was a jigsaw puzzle exercise, the dependent variable was an increase in the muscle strength of the upper limb. The population was 31 stroke patients with a sample of 12 treatment group patients and 11 control group patients using the simple random sampling method, the research instrument was an observation sheet. The results of the study with paired T test showed p value 0,000 <α = 0.05 indicating that there were differences in Jigsaw Puzzle exercises in the treatment group. While the results of research with the paired T test obtained p value 0.006 <α = 0.05 indicates that there were differences in the control group. From the results of the Independent T test different test showed p value = 0.027< 0.05 so it can be concluded that there is difference in the treatment and control groups. Jigsaw Puzzle exercises can be applied by stroke patients, both at home, and can be applied in hospitals or health centers for outpatient care in order to increase the strength of upper limb muscles in stroke patients.